2019
DOI: 10.1111/jth.14606
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic heparin mimetic that allosterically inhibits factor XIa and reduces thrombosis in vivo without enhanced risk of bleeding

Abstract: Background Human factor XIa (FXIa) is an actively pursued target for development of safer anticoagulants. Our long‐standing hypothesis has been that allosterism originating from heparin‐binding site(s) on coagulation enzymes is a promising approach to yield safer agents. Objectives To develop a synthetic heparin mimetic as an inhibitor of FXIa so as to reduce clot formation in vivo but not carry high bleeding risk. Methods We employed a gamut of methods involving synthetic chemistry, biophysical biochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…For some time now, we have been pursuing non-polymeric, non-saccharide mimetics of heparin/heparan sulfate as anti-viral [50][51][52][53][54], anti-cancer [55,56], and anti-thrombotic agents [57,58]. The advantage with these mimetics is that these are fully synthetic, easily characterizable, and highly amenable to advanced rational drug design possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some time now, we have been pursuing non-polymeric, non-saccharide mimetics of heparin/heparan sulfate as anti-viral [50][51][52][53][54], anti-cancer [55,56], and anti-thrombotic agents [57,58]. The advantage with these mimetics is that these are fully synthetic, easily characterizable, and highly amenable to advanced rational drug design possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The unique aspect of SPGG is its globular structure that theoretically can interact with diverse HS-binding proteins. In fact, our earlier work on SPGG has shown that it interacts with coagulation factor XIa [57,61] and glycoprotein gD [50], two completely different HS-binding proteins. Thus, we reasoned that the probability of targeting multiple proteins involved in cellular entry of HCMV, e.g., glycoprotein gB, PDGF-R, EGF-R, and neuropilin, would be higher with SPGG than with other non-saccharide mimetics developed so far.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic scheme of the NSGMs was previously reported [ 30 , 31 , 38 , 39 , 40 , 41 ]. All the molecules were characterized by NMR and ultra-performance liquid chromatography (UPLC) − electrospray ionization mass spectrometry (ESI-MS).…”
Section: Methodsmentioning
confidence: 99%
“…These molecules, referred to as non-saccharide GAG mimetics (NSGMs), have now been shown to bind and functionally modulate multiple GAG-binding proteins [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. For example, distinct NSGMs have been identified as ligands of fibroblast growth factor receptor-1 [ 28 ], antithrombin [ 33 , 34 ], neutrophil elastase [ 29 ], coagulation factor Xia [ 30 , 35 ], plasmin [ 31 ], and viral glycoprotein D [ 32 ], each of which are known to bind to heparin. In fact, several NSGMs have been found to display one-to-one correspondence with specific GAG sequences [ 28 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation